Tyrosine supplementation is ineffective in facilitating soccer players' physical and cognitive performance during high-intensity intermittent exercise in hot conditions. - Kate J Donnan; Emily L Williams; Nicholas Stanger (PLoS ONE)
Tyrosine has been proposed to potentially provide ergogenic benefits to cognitive and physical performance in physiologically demanding environments. However research into its effectiveness on cognitive and physical performance during exercise in the heat has revealed mixed findings. This study examined the effects of a commonly employed dosage of tyrosine supplementation on soccer players' physical and decision-making performance, cognitive appraisal, and affective states, during prolonged high-intensity intermittent exercise in hot conditions. Eight trained male soccer players completed a 92-minute high-intensity intermittent cycling sprint protocol whilst responding to soccer-specific decision-making tasks at various time points in 32°C (50%rh), in two counterbalanced conditions; tyrosine (150mg.kg-1) and placebo. No differences were found for peak power output (p = .486; 715 ± 98W vs 724 ± 98W, respectively), decision-making (p = .627; 86.9 ± 10.7% vs 88.6 ± 7.0%, respectively), cognitive appraisal (p = .693, 0.90 ± 0.42 vs 0.88 ± 0.39, respectively) nor affective states (p = .918; 1.15 ± 1.55 vs 1.14 ± 1.70, respectively) between tyrosine and placebo conditions. Also, no condition by time interaction effects were noted for these outcomes. In sum, tyrosine supplementation was ineffective for facilitating prolonged intermittent sprint (self-paced) activity, soccer-specific decision-making, and in alleviating perceptual strain, for soccer players' exercising in the heat. However, future research may wish to consider alternative approaches for tyrosine supplementation (e.g., timing, dosage) or induce heightened physiological strain to extend on these findings.